Pola Pikir Religius Tokoh Islam Berdampak Pada Pemikiran Masyarakat dalam Novel Dahlan Karya Haidar Musyaffa dan Penakluk Badai Karya Aguk Irawan MN - Ilmi, Fathya Madinatul (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to describe the religious mindset of Islamic leaders impacting community thinking in Haidar Musyaffa Dahlan novel and Aguk Irawan MN Penakluk badai and novels of relevance analysis. This research is a qualitative research descriptive presentation of data. Data obtained through literature study method. The novel Storm Conqueror by Aguk Irawan MN is the main character in the founding of NU. On the other hand, this novel explains the closeness of his harmonious relationship with Kiai Ahmad Dahlan who is the founder of Muhammadiyah. The data in this study were analyzed by describing the mindsets of Islamic religious leaders having an impact on people’s thinking in the novels Dahlan by Haidar Musyaffa and Peconluk Hurricane by Aguk Irawan MN and their relevance.